PENGARUH LOYALITAS MEREK, RUMOR, DAN COUNTRY OF ORIGIN TERHADAP KEPERCAYAAN MEREK - Jony Oktavian Haryanto; Tirza Florence Manurip (Media Riset Bisnis & Manajemen, 2011)
In this globalization era, the brand competition can not be avoided from the marketers to be able to keep their products loved by consumers. Therefore, the marketers have to create strategy to make the consumers trust in their brand product so they could compete in the marketplace because brand trust is so important. There must be positive value from a brand so that consumers will always be loyal to consume it because brand loyalty is so influential to brand trust. "Oreo" is a snack product in Indonesia which comes from USA, a country that is famous for its high quality food products. However, once heard negative rumor in public about Oreo and it had a very bad effect to the company because the decrease of public's brand trust to this product. The purpose of this research is to identify how the brand loyalty, rumor, and country of origin influence the brand trust. The writer obtained the samples from two hundreds respondents from Salatiga and Semarang by accidental sampling tecnique. The results of this research showed that the brand loyalty, rumor, and country of origin have significant effect to the brand trust of "Oreo". This result supports the writer's hypothesis which is proposed this research.Keywords : Brand loyalty, Rumor, Country of origin, Brand trust